Sponge-Derived Kocuria and Micrococcus spp. as Sources of the New Thiazolyl Peptide Antibiotic Kocurin - Olga Genilloud; Fernando Reyes; Francisca Vicente; Russell T. Hill; Matthew Anderson; José Rubén Tormo; Jesús Martín; Mercedes de la Cruz; Ignacio González; Sara Palomo (Marine Drugs, 2013)
Forty four marine actinomycetes of the family Microccocaceae isolated from sponges collected primarily in Florida Keys (USA) were selected from our strain collection to be studied as new sources for the production of bioactive natural products. A 16S rRNA gene based phylogenetic analysis showed that the strains are members of the genera Kocuria and Micrococcus. To assess their biosynthetic potential, the strains were PCR screened for the presence of secondary metabolite genes encoding nonribosomal synthetase (NRPS) and polyketide synthases (PKS). A small extract collection of 528 crude extracts generated from nutritional microfermentation arrays was tested for the production of bioactive secondary metabolites against clinically relevant strains (Bacillus subtilis, methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter baumannii and Candida albicans). Three independent isolates were shown to produce a new anti-MRSA bioactive compound that was identified as kocurin, a new member of the thiazolyl peptide family of antibiotics emphasizing the role of this family as a prolific resource for novel drugs.